The Nationalism Attitudes of Students at Tanzil Village Lindungan School in Malaysia - Farida Safitri; Nurmelinia Nurmelinia; Nurul Hidayah; Wariyatun Wariyatun (Asosiasi Lembaga Pendidikan Tenaga Kependidikan Peguruan Tinggi Muhammadiyah dan Aisyiyah, 2023)
Indonesian children living abroad face challenges in maintaining their national identity due to exposure to different cultures. Therefore, this research aims to analyze the implementation of character education in Indonesian schools abroad and how the internalization of nationalist values is done in children. The research was conducted at SD At Tanzil Kampung Lindungan, Malaysia, which is one of the Indonesian schools abroad. This study was conducted in the academic year 2022/2023 using a qualitative method. Data collection techniques included observation, interviews, and documentation. The results of the study show that the school employs three main methods to internalize nationalist values in children, namely: 1) traditional games to enhance unity awareness, 2) singing to instill Pancasila values, and 3) teaching heroism values through stories. This research also found that instilling nationalism in young children, such as Early Childhood Education (ECE), requires an engaging approach that is suitable for their cognitive development. Educators who use creative methods such as traditional games and singing can help children internalize nationalist values more easily and enjoyably. The role of schools and educators is crucial in keeping Indonesian children abroad connected to their culture and national values.